Complex formation between 3;3´-diethylthiacarbocyanine iodide and DNA and its investigation in aqueous solution - M. Y. Anikovsky; A. S. Tatikolov; V. A. Kuzmin (International Journal of Photoenergy)
The binding of 3;3′-diethylthiacarbocyanine iodide (DTCC) with molecules of DNA was investigated by different photochemical methods. Absorption spectra were investigated under various concentration of DNA. Isosbestic points observed in these spectra are attributable to existence of two different complexes DTCC with DNA. Equilibrium constants of the formation of complexes I and II were determined (K1≈106M−1, K2≈5×104M−1 accordingly). Differential absorption spectra of two photoisomers of DTCC were obtained by flash photolysis method; it was found that the quantum yield of the short-lived photoisomer decreases and the quantum yield of the second long-lived photoisomer builds up with the increase in the DNA concentration. Kinetics of interaction between the triplet state of the dye and oxygen were investigated under various concentration of DNA. The growth of the quantum yield of fluorescence and intersystem crossing was observed with the increase in the DNA concentration.